2014
DOI: 10.1371/journal.pone.0097431
|View full text |Cite|
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms Reveal Genetic Structuring of the Carpathian Newt and Provide Evidence of Interspecific Gene Flow in the Nuclear Genome

Abstract: Genetic variation within species is commonly structured in a hierarchical manner which may result from superimposition of processes acting at different spatial and temporal scales. In organisms of limited dispersal ability, signatures of past subdivision are detectable for a long time. Studies of contemporary genetic structure in such taxa inform about the history of isolation, range changes and local admixture resulting from geographically restricted hybridization with related species. Here we use a set of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 99 publications
3
47
1
Order By: Relevance
“…; Zielinski et al . ). Previous studies have shown that polyploidy (LLR and LRR, very rarely tetraploidy) in P. esculentus occurs frequently and across different population systems (including mixed systems with P. lessonae and P. ridibundus , or both) in Ukraine and Russia (Borkin et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Zielinski et al . ). Previous studies have shown that polyploidy (LLR and LRR, very rarely tetraploidy) in P. esculentus occurs frequently and across different population systems (including mixed systems with P. lessonae and P. ridibundus , or both) in Ukraine and Russia (Borkin et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Zieliński et al . , ). While Lm is also genetically structured, this structure is relatively shallow (Zieliński et al .…”
Section: Methodsmentioning
confidence: 99%
“…While Lm is also genetically structured, this structure is relatively shallow (Zieliński et al . , ), and thus, here we consider all Lm as a single genetic lineage. To minimize the confounding effects of population structure, we randomly subsampled one gene copy per population, resulting in 26 Lm and 32 Lv gene copies per locus in the ABC data set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence for genetic exchange between them after the divergence dated to the Pliocene (Nadachowska-Brzyska et al 2012; Pabijan et al 2015). Lissotriton montandoni has however exchanged genes with other evolutionary lineages of L. vulgaris (Lv, Babik et al 2005; Nadachowska-Brzyska et al 2012; Zieliński et al 2013, 2014, 2016). The higher MHC class II variation in Lm has been attributed to introgression from Lv (Nadachowska-Brzyska et al 2012).…”
Section: Introductionmentioning
confidence: 99%